Dynamic supply chain coordination games with repeated bargaining. (February 2015) - Brusset, Xavier; Agrell, Per J.
Highlights: A supplier will behave opportunistically to extract a rent from his customer. The customer mis-represents the costs of dealing with the supplier to protect his rent. The supply chain's efficiency is affected even though opportunistic behavior is absent. Dual-sourcing finds further justification here. Abstract: Coordination in a supply chains may require investment in relationship-specific assets (RSA) including information systems and human resources from all or a subset of the partners. These investments are typically partially non-verifiable, possibly based on internal resources or opportunity costs. A supplier offers a single-price single-period contract to a downstream manufacturer who accepts or turns to a non-strategic outside option. Both parties invest in relationship-specific assets (RSA) accordingly. Using a game theoretic framework of repeated single-period bargaining under asymmetric information and outside options, we show how a supplier may behave opportunistically. We show how this rent extraction threat is mitigated when the manufacturer mis-informs the supplier or hides information from her. As a result of both behaviors, our model explains how supply chain coordination and efficiency are impaired. On a normative basis, we provide the manufacturer with new justifications for both dual sourcing and distorting information. Numerical examples illustrate the results.